IMPLEMENTATION OF PROBLEM SOLVING METHOD TO IMPROVE STUDENTS' COGNITIVE ASPECTS IN PAI SUBJECTS AT SMP JATI AGUNG TAMAN SIDOARJO - Afifah Afifah; Imam Mashuri (INCARE, International Journal of Educational Resources, 2023)
The background of this research is to provide opportunities for students to participate in solving problems that are studied between individuals and groups in solving problems given by the teacher. The aim is to find out the stages of implementing the problem solving method in PAI subjects, to find out the cognitive aspects of students after the problem solving method is applied to PAI subjects and to find out the supporting factors and inhibiting factors in implementing the problem solving method to improve students' cognitive aspects in subjects PAI at SMP Jati Agung Taman Sidoarjo. The method used in this research is descriptive qualitative, using interview, observation and documentation techniques. Interactive analysis which includes three components, namely data reduction, data presentation, and data verification or drawing conclusions. The results showed that the stages of implementing the problem solving method in PAI subjects began with identification, representation/presentation, planning for solving, implementing, assessing planning, assessing the results of solving. Students' cognitive aspects increased after the problem solving method was applied, factors that supported the implementation of problem solving methods to improve students' cognitive aspects in PAI subjects, namely students' intellectual abilities, the active role of teachers and students in teaching and learning activities. The inhibiting factors are lack of student motivation, lack of teacher support, and students who are afraid or don't dare to express their opinions.